2003
DOI: 10.1097/00006231-200302000-00012
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-SnF2 colloid ‘LLK’: particle size, morphology and leucocyte labelling behaviour

Abstract: 99mTc-SnF2 colloid (Radpharm LLK) leucocyte labelling agent is used in whole blood, exploiting phagocytosis. The objectives of this work were to optimize leucocyte labelling in leucocyte-enriched plasma, and to investigate: (i) the effect of temperature and other factors on labelling efficiency; (ii) the selectivity for different leucocyte types; (iii) the viability of the labelled cells and efflux of the radiolabel; and (iv) the physical characteristics of the colloid. Density gradient centrifugation was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…These particles contain Sn, but not significant amounts of Cl, as previously described using SEM and energy-dispersive X-ray analysis (EDAX) [9]. McClelland also reported that, in addition, the particles contain O but not F [9], suggesting they consist primarily of stannous oxide. The majority of the Cl found in the TcSn colloid solution residue after dehydration is in separate NaCl salt crystals [9].…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…These particles contain Sn, but not significant amounts of Cl, as previously described using SEM and energy-dispersive X-ray analysis (EDAX) [9]. McClelland also reported that, in addition, the particles contain O but not F [9], suggesting they consist primarily of stannous oxide. The majority of the Cl found in the TcSn colloid solution residue after dehydration is in separate NaCl salt crystals [9].…”
Section: Discussionsupporting
confidence: 71%
“…Hence, the most likely explanation for the subcellular association of Sn with Fe found in our study is that the TcSn colloid-containing phagosomes fuse with neutrophil granules, and more specifically the gp91 PHOX -containing specific granules, within the first hour after phagocytosis. However, previous studies have shown that there is no evidence of neutrophils undergoing the respiratory burst as a result of TcSn colloid labelling [4,5,9,12]. Hence, despite the colocalisation of at least one of the components of the NADPH oxidase to the TcSn colloid-containing phagosomes, this system is not activated.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations